The Effect of Current Accounts, Savings and Time Deposits on Banking Credit: A Case Study of Regional Development Banks (RDB) in Indonesia - Zulfikar Hasan (Journal of International Business, Economics and Entrepreneurship)
This study aims to examine the effect of Current Accounts, Savings, and Time Deposits on Banking Credit of Regional Development Banks (BPD) in Indonesia. The data in this study are in the form of quarterly reports from Regional Development Banks (BPD) in Indonesia. Current Accounts, Savings, and Time Deposits on Banking Credit of Regional Development Banks (BPD) in Indonesia is expected to be evident in 2019–2022. The research method used is the panel regression method. The outcomes show that current accounts, savings and time deposits influences the credit of bank BPD. R Settled 0.994461 current accounts, savings and time deposits factors influence bank credit. The Adjusted R Squared value of 0.994461 indicates that the independent variables can explain the dependent variable 99.44% of the time, while other factors not included in the model have an impact on the remaining 0.5539%. This means that 99.44% of the variable Savings and Time Deposits can predict bank credit, while the remaining 0.5539 percent is impacted by other factors not investigated in this study. This result serves as a warning to BPD banks in each province to be careful in extending credit to customers, because when credit increases, current accounts, savings and time deposits also increase. And if credit decreases, it's the other way around. This means that the higher the credit given to customers, the banking income will also increase with the help of increased current accounts, savings and time deposits. The significance and implications of the results of this research can provide an illustration that although regional banks (BPD) still have an impact on the Indonesian economy even though they only provide samples in the form of savings products.